2000
DOI: 10.1677/joe.0.1650157
|View full text |Cite
|
Sign up to set email alerts
|

Increased maternal serum activin A but not follistatin levels in pregnant women with hypertensive disorders

Abstract: Activin A levels are elevated in maternal serum of pregnant women with hypertensive disturbances. Because follistatin is a circulating binding protein for activin A, the present study was designed to evaluate whether serum follistatin and activin A levels also change in patients with hypertensive disorders in the last gestational trimester. The study design was a controlled survey performed in the setting of an academic prenatal care unit. Healthy pregnant women (controls, n=38) were compared with patients suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 21 publications
5
39
1
1
Order By: Relevance
“…Although no markedly elevated circulating levels of activin A and inhibin A were observed in women with IUGR, analysis of the longitudinal data suggested that activin A levels may be modestly increased (Keelan et al 2002). Additionally, small fetuses did not significantly modify the inhibin and activin concentrations in pregnancies complicated by preeclampsia (D'Antona et al 2000;Florio et al 2002). Furthermore, inhibin and activin concentrations in fetal circulation levels did not change in presence of IUGR (Debieve et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Although no markedly elevated circulating levels of activin A and inhibin A were observed in women with IUGR, analysis of the longitudinal data suggested that activin A levels may be modestly increased (Keelan et al 2002). Additionally, small fetuses did not significantly modify the inhibin and activin concentrations in pregnancies complicated by preeclampsia (D'Antona et al 2000;Florio et al 2002). Furthermore, inhibin and activin concentrations in fetal circulation levels did not change in presence of IUGR (Debieve et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Maternal serum levels of activin A increase from about mid-pregnancy to a peak close to term (Muttukrishna et al 1996, Fowler et al 1998, Schneider-Kolsky et al 2002, falling quickly after birth (Fowler et al 1998). In pregnancies complicated by placental dysfunction as evidenced by intrauterine foetal growth restriction (Bobrow et al 2002, Barkehall-Thomas et al 2006 or preeclampsia (Muttukrishna et al 1997, D'Antona et al 2000, Manuelpillai et al 2001, Silver et al 2002, maternal serum levels of activin A are significantly higher than observed in normal pregnancy. While these increased circulating levels of activin A are thought to arise from increased placental production (Manuelpillai et al 2001, Silver et al 2002) the mechanism(s) underlying such increased placental output remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are two major isoforms of FST, FST288, which is anchored to the cell surface by interactions with heparin sulfate proteoglycans (9), and FST315, which is the predominant form found in circulation. In humans, aberrant expression of FST and activins are implicated in infertility; dysregulation of FST, activins, and inhibins was reported in women with impending abortion (10), recurrent miscarriage (11,12), hypertensive disorders during pregnancy (13), and repeated implantation failure after in vitro fertilization (14). However, the role that FST plays in normal pregnancy remains uncertain.…”
mentioning
confidence: 99%